PENGARUH BUERGER ALLEN EXERCISE TERHADAP NILAI ANKLE BRACHIAL INDEX PADA PASIEN DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS BANDAR KHALIPAH MEDAN - Erni Trirenna Sihombing; Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
Diabetes mellitus is one of four non-communicable diseases which is a priority for follow-up. One of the complications of Diabetes is the signs and symptoms of problematic peripheral blood vessels so appropriate management is needed to reduce complications. Therefore, Buerger The Allen Exercise is a varied movement exercise for the lower extremities that uses gravitational force which is done slowly and consistently and can increase the Ankle Bracial Index (ABI) score and can influence the ABI score to be better than before. Objective: to analyze the effect of the Buerger Allen Exercise on the Ankle Brachial Index value in Diabetes Mellitus patients in the Bandar Khalipah Health Center working area, Medan. Method: this type of research is quantitative with a quasi-experimental design with a two group pre test-post test design, sample collection technique using purposive sampling technique with a total of 24 respondents. Analysis of research data used the Wilxocon sign rank test. Result: The results of this study show that there is an influence of Buerger Allen Exercise on the Ankle Brachial Index value in Type 2 Diabetes Mellitus patients in the working area of the Bandar Khalipah Community Health Center with a p-value of 0.009 <0.05. Conclusion: there is a significant effect of Buerger Allen Exercise on the Ankle Brachial Index value in Type 2 Diabetes Mellitus patients in the working area of the Bandar Khalipah Community Health Center. Suggestion: It is hoped that future researchers will modify the method and have a larger sample size as well as a longer intervention to obtain more accurate results so that they can add broader insight into independent nursing interventions.